FREIBURG FRAGMENTS OF A MS OF THE PELAGIAN COMMENTARY ON THE EPISTLES OF ST PAUL - Souther, Alex (The journal of theological studies, 1912)
ALEX SOUTHER; FREIBURG FRAGMENTS OF A MS OF THE PELAGIAN COMMENTARY ON THE EPISTLES OF ST PAUL, The Journal of Theological Studies, Volume os-XIII, Issue 52, 1